2017
DOI: 10.9734/ajeba/2017/33866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of International Public Sector Accounting Standards (IPSAS) Adoption on Financial Accountability in Selected Local Governments of Oyo State, Nigeria

Abstract: The study evaluated the impact of International Public Sector Accounting Standard (IPSAS) on the financial accountability of selected local governments of Oyo State, Nigeria. The impact of IPSAS adoption on corruption reduction, transparency and accountability in the selected Local Governments were critically examined. The study which adopted survey design collected data using five point likert-scale questionnaires which was administered on sample of 105 Accountants and Internal Auditors in the selected local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 3 publications
6
14
0
Order By: Relevance
“…In agreement with our findings, past studies concluded that the existence of technical support from qualified accountants adds value in implementation of accrual-based IPSAS [1,27,13,5]. Moreover, Abimbola [60] and Whitefield [27] documented that, there is a need for the government to increase the employment of qualified accountants in the LGAs. This influence successful implementation of accrualbased IPSAS in the LGAs.…”
Section: Factors Influencing Implementation Of Accrual-based Ipsas Insupporting
confidence: 91%
“…In agreement with our findings, past studies concluded that the existence of technical support from qualified accountants adds value in implementation of accrual-based IPSAS [1,27,13,5]. Moreover, Abimbola [60] and Whitefield [27] documented that, there is a need for the government to increase the employment of qualified accountants in the LGAs. This influence successful implementation of accrualbased IPSAS in the LGAs.…”
Section: Factors Influencing Implementation Of Accrual-based Ipsas Insupporting
confidence: 91%
“…Thus, the application of government accounting standards in the preparation of financial statements will provide assurance that the financial statements prepared have the qualifications of financial information that is useful for the users who need it. The results of this study are in line with Diniz's (2015) research, Abimbola et al (2017), and Mhaka (2014) which stated that government accounting standards have an effect on regional financial accountability.…”
Section: Discussion (Interpretation)supporting
confidence: 89%
“…Better execution of the presentation of financial statements will have implications for increasing accountability in the financial management of Kulon Progo Regency. The results of this study are in line with the results of Chinedu et al (2016), Chan (2010), Ohaka et al (2016, and Bello in Abimbola (2017). The three studies stated that the presentation of regional financial statements had a positive effect on the accountability of regional financial management.…”
Section: B the Effect Of Presentation Of Regional Financialsupporting
confidence: 91%
See 2 more Smart Citations